BUILDING A NUTRITION COACHING FRAMEWORK WITHIN A COLLEGIATE RECREATION CENTER - Rojas, Mitzie (My University, 2025)
My applied practical experience (APE) consisted of building a nutrition coaching framework within a collegiate recreation center. The aim of this project nutrition was to develop a nutrition coaching framework within a collegiate recreation center to support student health and well-being through evidence-based nutrition education and personalized coaching. Based on collegiate student national data and university data, the nutrition coaching framework was designed to address college students' unique needs by integrating tailored coaching to better provide guidance for behavior change strategies. This nutrition coaching framework fulfilled at least 6 master’s in public health (MPH) competencies by assessing population needs, designing a coaching structure, building partnerships, and building tools to help with implementation. My coursework along with my products met several learning objectives by applying public health principles to program creation, professional development, implementation, and assessment. This framework also has the potential to contribute to the Health Promoting University areas of focus related to social connection and university engagement. Overall, this nutrition coaching framework can potentially establish a model for integrating nutrition coaching into a collegiate recreation setting, a place that students are familiar with and complements their physical activity levels.
Keywords: Nutrition coaching; College students; Recreation center; Social determinants of health (SDOH); Motivation interviewing; Transtheoretical model